LANGUAGE POLICIES AND ECONOMIC INEQUALITY: AN ANALYTICAL PERSPECTIVE - Tursunova Ozodaxon To’raxon qizi; Tursunxo‘jayeva Moxigul Maxmud qizi (Ustozlar uchun, 2025)
Language policies profoundly shape socioeconomic dynamics, acting as both a bridge and a barrier in accessing economic opportunities. This paper investigates the role of language policies in perpetuating or reducing economic inequalities through a review of existing literature and a comparative case study analysis. The findings reveal that inclusive policies foster equity, whereas exclusionary practices deepen disparities.